PKM Desa Wisata Sehat: Outbound dan Edukasi Kesehatan - Sitti Nur Djannah; Surahma Asti Mulasari; Sulistyawati Sulistyawati; Tri Wahyuni Sukesi; Fatwa Tentama (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Jurug Gede Waterfall is a new tourist destination in Gunungkidul due to accessibility and close access to other destinations. This location relies on a not permitted waterfall; consequently, in the dry season, the waterfall can not exist as a tourist view. In another side, in surrounding the waterfall, available a lot of natural resources such as bamboo and wood that can be used as an alternative to building something creative for the tourist destination. Along with the presence of Jurug Gede as a tourist destination, it is essential to equip the indigenous people with sufficient knowledge on health to prevent the negative impact of tourism development such as knowledge on the individual hygiene, environmental health and personal health. PKM was carried out in several stages: socialization with partners, community and related parties, training and workshop. The solutions offered by the PKM program include three main things: empowering local potentials, improving the quality of managers in healthy tourism management and improving the quality of human resources supporting tourism (surrounding residents). The three main activities will be carried out through community empowerment, training, workshops and infrastructure support. The targeted outputs of this PKM are: 1) the increase in partner assets, in this case, is 4 outbound vehicles that can be used without relying on the season, 2) increasing the health knowledge of the surrounding community, 3) publication in 2 national journals and 1 proceeding of local scientific meeting, 4) press releases in local media and, 5) videos.